Conservative Management of Placenta Accreta/Increta after Vaginal Birth - Peiffer, S.; Reinhard, J.; Reitter, A.; Louwen, F. (Geburtshilfe und Frauenheilkunde, 2012)
Aim: Aim of the study was to show that conservative management with preservation of the uterus and of fertility is possible in patients with placenta accreta/increta after vaginal delivery. Method: A retrospective analysis of patients with placental attachment disorders after vaginal delivery was done in a perinatal centre between November 2009 and April 2011. The patient collective was identified using the ICD-10 codes for placenta accreta/increta/percreta, and patient records were analysed for risk factors, maternal morbidity, preservation of the uterus and of fertility, and neonatal outcome. Results: Three cases of placenta increta were identified in the last 1.5 years out of a total of 1457 vaginal deliveries, and all 3 cases were treated conservatively. Mean maternal age was 35.3 years; gestational age ranged from 39 to 41 weeks, and mean duration between delivery of the child and delivery of the placenta was 44.67 days (range: 14–100 days). Two patients developed symptoms of endomyometritis, including fever, leukocytosis and increased CRP levels. All 3 women were successfully managed with preservation of the uterus. Conclusion: In selected cases with placenta accreta/increta after vaginal delivery, it is possible to avoid surgical procedures, particularly hysterectomy procedures, and successfully manage these patients conservatively with preservation of the uterus.
Keywords: placenta accreta/increta; conservative management; outcome